2017
DOI: 10.1007/s10461-017-1930-3
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hardship, Condomless Anal Intercourse and HIV Risk Among Men Who Have Sex with Men

Abstract: The objective of this study was to examine the association between financial hardship, condomless anal intercourse and HIV risk among a sample of men who have sex with men (MSM). Users of a popular geosocial networking application in Paris were shown an advertisement with text encouraging them to complete a anonymous web-based survey (n = 580). In adjusted multivariate models, high financial hardship (compared to low financial hardship) was associated with engagement in condomless anal intercourse (aRR 1.28; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Financial hardship among MSM is shown to be associated with a higher likelihood of participating in sexual risky situations (eg, alcohol or drug use before or during sex), condomless anal intercourse, transactional sex and drug use. [28][29][30] These findings confirm that among MSM, a subgroup can be identified that is vulnerable for acquiring HIV or other STIs. We recommend HIV and STI prevention organisations to provide guidance on how to reduce the risk for HIV infections and STIs when engaging in sexual practices such as group sex, chemsex or sex work.…”
Section: Discussionsupporting
confidence: 68%
“…Financial hardship among MSM is shown to be associated with a higher likelihood of participating in sexual risky situations (eg, alcohol or drug use before or during sex), condomless anal intercourse, transactional sex and drug use. [28][29][30] These findings confirm that among MSM, a subgroup can be identified that is vulnerable for acquiring HIV or other STIs. We recommend HIV and STI prevention organisations to provide guidance on how to reduce the risk for HIV infections and STIs when engaging in sexual practices such as group sex, chemsex or sex work.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, young MSM were more likely to have sexual risk behaviors and have lower utilization of mental health care, which may further aggravate their psychological problem [46]. Personal income is also associated with depression, which might be partially explained by the financial hardship, discrimination and social stress related to poverty [47]. Mental health interventions and services therefore should be prioritized for younger and poorer MSM, who might be more vulnerable and lack of resources to cope with mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study showed that in one personal resource construct, education did not have an impact on information or behavioral skills [23]. Low-income individuals may be more likely to encounter stressors and/or limit their access to resources to buffer against these stressors [51]. Individuals with socioeconomic disadvantages utilize their limited cognitive coping resources in dealing with these excess stressors, especially lack of social support, leading to engagement in condomless sexual behaviors [31].…”
Section: Discussionmentioning
confidence: 99%